Genetic variability in Tambaqui generations of the breeding program in the Central-West Region of Brazil - Urrea-Rojas, Angela Maria; Bignardi, Annaiza Braga; Souza, Felipe Pinheiro de; Lima, Ed Christian Suzuki de; Ayres, Denise Rocha; Povh, Jayme Aparecido; Moraes Neto, Américo; Yamachita, Andrei Lincoln; Alves, Mariana Stucki; Lopera-Barrero, Nelson Mauricio (Semina: Ciências Agrárias, 2021)
The implementation of fish breeding programs in Brazil has brought significant results in the productivity of tilapia. However, the insertion of native species with great potential (such as Tambaqui Colossoma macropomum) in these programs is still recent, and thus requires genetic information for monitoring and enabling their consolidation into the programs. The objective of the present study was to evaluate the genetic diversity of the parental generation (G0) and two consecutive generations (G1 and G2) in the C. macropomum genetic improvement program, located in the municipality of Sorriso, Mato Grosso, Brazil. Ninety caudal fin samples were collected (30 samples per generation) for DNA extraction. The genetic study implemented seven microsatellite markers (Cm1A8, Cm1A11, Cm1D1, Cm1E3, Cm1F4, Cm1F5, and Cm1H8). A total of 17 alleles were amplified, with variations in the mean number between four to two alleles per locus. The size per locus ranged from 170 to 360 bp. The average inbreeding coefficient was 0.126 (G0), -0.040 (G1), and 0.131 (G2). No null or exclusive alleles were found. The observed heterozygosity values for G1 and G2 demonstrated the preservation of genetic variability (0.453 and 0.409, respectively). In conclusion, the genetic diversity of the parental generation (G0) and the two progenies generations (G1 and G2) were adequate, which demonstrates that the genetic improvement program was conducted correctly; however, it is important to continue to evaluations the genetic diversity of the future progeny.